Identification and characterization of a supraclavicular brown adipose tissue in mice - Mo, Qianxing (JCI Insight, 2017)
A fundamental challenge to our understanding of brown adipose tissue (BAT) is the lack of an animal model that faithfully represents human BAT. Such a model is essential for direct assessment of the function and therapeutic potential of BAT depots in humans. In human adults, most of the thermoactive BAT depots are located in the supraclavicular region of the neck, while mouse studies focus on depots located in the interscapular region of the torso. We recently discovered BAT depots that are located in a region analogous to that of human supraclavicular BAT (scBAT). Here, we report that the mouse scBAT depot has morphological characteristics of classical BAT, possesses the potential for high thermogenic activity, and expresses a gene signature that is similar to that of human scBAT. Taken together, our studies reveal a mouse BAT depot that represents human BAT and provides a unique tool for developing new translatable approaches for utilizing human scBAT.